EFFECTIVENESS OF MIND-MAPPING TEACHING STRATEGY IN ENHANCING SENIOR SECONDARY SCHOOL STUDENTS’ ACHIEVEMENT AND INTEREST IN COMPUTER STUDIES (UNIZIK Journal of STM Education, 2019)
The effectiveness of mind-mapping teaching strategy in enhancing senior secondary school students’ achievement and interest in computer studies of Owerri municipal council of Imo State was determined. Six research questions guided the study while six hypotheses were formulated and tested at 0.05 level of significance. The design adopted for the study was the quasi-experimental, non-equivalent pre-test and post-test control design. The population is made up of 1,052 Senior Secondary Two (SS II) Computer studies students found in the 4 co-educational schools within Owerri Municipal Council of Imo State in 2017/2018 academic session. The sample of the study consisted of 105 SS II students which was sampled through purposive and multistage sampling technique. Data were collected using researcher-made Computer Studies Achievement Test (CSAT) and Computer Studies Interest Inventory (CSII). The reliability coefficients obtained for the CSAT and the CSII were 0.84 and 0.72 using Kuder Richardson formula-20 and Cronbach alpha procedure respectively. Data collected were analysed using mean and standard deviation to answer the research questions while Analysis of Covariance (ANCOVA) was used to test the hypotheses. Findings indicated significant effect of mind-mapping over the conventional strategy in CSAT and CSII (P < 0.05). Gender (p> 0.05) was not significant factor in determining students' achievement and interest in mind-mapping group. Results further indicated a significant interaction effect of teaching strategy and gender (P < 0.05), both in CSAT and CSII. Based on the findings, it was recommended among others that computer studies teachers should use mind-mapping strategy to improve students’ achievement and interest in computer studies irrespective of their gender.
Keywords: Computer Studies; Achievement; Interest; Mind-Mapping Strategy